Self-Directed Learning and Digital Literacy in Social Studies Learning: Efforts to Improve Students’ Critical Thinking - Fadli, Muhammad Rijal; Mujazi, Mujazi; Syofyan, Harlinda; Rosyid, Ainur (Pedagogika, 2024)
This research aims to analyze the influence of self-directed learning (X1) and digital literacy (X2) on students’ critical thinking (Y) in social studies learning. This quantitative research method uses structural equation modeling (SEM) data analysis assisted by the SMARTPLS 3.0 application program. The research results explain that self-directed learning and digital literacy positively and significantly affect students’ critical thinking in social studies learning so that it is no longer boring.